Humanitarianism and Asylum: The Ambiguous Governance of International Protection in Madrid from the Perspective of Institutional Actors - Cortés Maisonave, Almudena (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2026)
The increase in the arrival of forcibly displaced people in the European Union has intensified the integration of security-oriented migration policies with humanitarian assistance policies, leading to the emergence of humanitarian borders. Research in this area has focused on external humanitarian borders, and much less on internal ones. The main analytical contribution of this article is the identification and conceptualisation of the ethnographic category of the “non-applicant” situated within the political and social context of an internal humanitarian border, as a tool for revealing the mechanisms of the ambiguous governance of international protection. To this end, I have drawn on an ethnographic study conducted in the city of Madrid between 2022 and 2024, based on 22 in-depth interviews, primarily with institutional actors (20 interviews with humanitarian workers from NGOs within the reception system and 2 with officials from the State Public Administration).
Keywords: anthropology; refuge; humanitarianism; reception